Chromosomal fusions trigger rediploidization of autopolyploid genomes - Chuanshuai Xie; Zitu Ma; Chaowei Zhou; Kexin Ma; Haoyu Wang; Jiahong Wu; Yan Zhou; Yongrui Lu; Da Ji; Xuedie Gu; He Gao; Junting Li; et al. (Nature, 2026)
Abstract The ancestor of all vertebrates is thought to have undergone autopolyploid whole-genome duplication (WGD) 1,2 , doubling the genetic raw material for evolutionary diversification 3–5 . However, we still do not understand the first steps of rediploidization that followed, required for the emergence and divergence of duplicated genes (ohnologues) created by WGD 6,7 . Consequently, how the functional potential created by autopolyploidy becomes realized during evolution remains unclear. Snow carps (Schizothoracine) have a history of recent WGDs and evolved high-altitude adaptations 8–10 , making these fish a particularly suitable system to study the early stages and consequences of rediploidization. Here genomic data from all snow carp genera reveal their autopolyploid origin, including tetraploids, hexaploids and one icosaploid (20 n ). We present haplotype-resolved genomes for two snow carp species ( Schizopygopsis younghusbandi and Schizothorax curvilabiatus ) from divergent lineages, revealing a single ancestral autotetraploidy event. Comparative genomic, meiotic pairing and allele composition analyses indicate that unbalanced chromosome fusions were responsible for the transition from tetrasomic to disomic inheritance, creating genomic regions harbouring diploid ohnologue pairs, with non-rearranged chromosomes remaining tetraploid. This study suggests that this mechanism initiated rediploidization and documents its early chromosomal and genomic consequences. It starts at chromosome fusion sites and expands outwards towards chromosomal arms, a process that remained incomplete post-speciation, leading to a mixture of ancestral and lineage-specific ohnologue divergence on highly syntenic chromosomes.